Dipsacus gmelinii (Caprifoliaceae), a wetland species new to the Bulgarian flora - Kunev, Georgi; Kostadinov, Ivan; Karakasheva, Daniela (Hacquetia, 2024)
Dipsacus gmelinii is here reported as a new addition to the vascular flora of Bulgaria. It was recorded on Belene Island, in the Danube River. In the present paper, the species is described morphologically with an emphasis on carpomorphological characters. The distinctive differences from related species of the genus are also highlighted. Additionally, ecological conditions and floristic composition at the localities of the species, and phytosociological relationships of the communities in which it participates are discussed.